2022
DOI: 10.3892/ol.2022.13620
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychavicol as a potential anticancer agent (Review)

Abstract: Piper betle leaves are widely cultivated in Malaysia, India, Indonesia and Thailand. They have been used as a traditional medicine for centuries due to their medicinal properties, including antioxidant, antiproliferative, antibacterial, antifungal and anti-inflammatory properties, which are attributable to their high phenolic contents. Hydroxychavicol (HC), a primary constituent of P. betle leaves, is known to possess antiproliferative activity at micromolar doses on various cancer cell lines of different orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The structure of hydroxychavicol contains catechol, which is known to have antiproliferative properties [3,4,[6][7][8]13,27,28]. Our study demonstrates that the presence of the catechol-like structure is key for the antiproliferative activity of hydroxychavicol and that the attachment of an aliphatic chain to the catechol structure dampens that activity (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The structure of hydroxychavicol contains catechol, which is known to have antiproliferative properties [3,4,[6][7][8]13,27,28]. Our study demonstrates that the presence of the catechol-like structure is key for the antiproliferative activity of hydroxychavicol and that the attachment of an aliphatic chain to the catechol structure dampens that activity (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
“…Its usage encompasses cultural, spiritual, and medical matters. Research has shown that this herb has antioxidative, anti-inflammatory, antibacterial, and anticancer properties [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep heart-shaped leaves of Piper betle, also known as betel leaves, are a natural source of hydroxychavicol (4-allyl-cat-epil, 1-allyl-3,4dihydroxybenzene), a significant phenolic component that has historically been utilized as a mouth freshener in eastern Asian native countries. It has been shown to possess the ability to trigger apoptosis in cells via the induction of oxidative stress, depletion of glutathione (GSH), and modulation of the cell cycle [11]. By stimulating the body's innate immunological response, hydroxychavicol also has anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychavicol, a phenyl propanoid compound isolated from the chloroform extraction of an aqueous extract of Piper betel leaves, showed inhibitory activity against oral cavity pathogens. Hydroxychavicol (HC), is known to possess antiproliferative activity at micromolar doses on various cancer cell lines of different origins while leaving normal cells unharmed 1 . It exhibited an inhibitory effect on all of the oral cavity pathogens tested (MICs of 62.5 to 500 g/ml) with a minimal bactericidal concentration that was two-fold greater than the inhibitory concentration 2 .…”
Section: Introductionmentioning
confidence: 99%